A semi-analytical method for elastic-plastic analysis of a deep-buried elliptical tunnel. (February 2022) - Ma, Yaocai; Lu, Aizhong; Cai, Hui; Zeng, Xiangtai
Abstract: The elastic–plastic problem of an elliptical tunnel is of great significance in engineering. Previous studies were mainly focused on the circular tunnel. An elastic–plastic analysis is performed for determining the plastic zone around a deep-buried elliptical tunnel subjected to far-field uniform in-situ stresses. The yielding of the rock mass obeys the Mohr-coulomb criterion. The elastic stress field is given by the complex variable method and the plastic stress field is numerically determined by the slip line theory. The solution is obtained according to the stress continuity condition along the elastic–plastic interface. Correspondingly, a set of nonlinear equations involves the mapping function coefficients is established and solved with the help of differential-evolution algorithm. The validity of the method is verified by comparing the results with the numerical simulation of FLAC3D software. Estimates of the size and shape of the plastic zone are then presented for varying parameters including in-situ stress, cohesion, internal friction angle and axis ratio.